(untitled) (Journal of Partial Differential Equations, 2008)
" In this note we consider the blow-up rate of solutions for p-Laplacian equation with nonlinear source, u_t=div(|2207u|^p-22207u)+u^q, (x,t)2208R^N00d7(0,T), N 2265 1. When q > p - 1, the blow-up rate of solutions is studied."